Nano-Liposomal Beetroot Phyto-Pigment in Photodynamic Therapy as a Prospective Green Approach for Cancer Management: In Vitro Evaluation and Molecular Dynamic Simulation - Doaa Abdel Fadeel; Maha Fadel; Abdullah Ibrahim El-Kholy; Ahmed A. El-Rashedy; Engy Mohsen; Marwa I. Ezzat; Marwa Y. Issa (MDPI AG, 2024)
Using plant extracts as photosensitizers in photodynamic therapy (PDT) represents a significant green approach toward sustainability. This study investigates beetroot juice (BRJ), betanin, and their liposomal formulations (Lip-BRJ, Lip-Bet) as photosensitizers in cancer PDT. BRJ was prepared, and its betanin content was quantified via HPLC. The p-nitrosodimethylaniline (RNO)/imidazole technique monitored the singlet oxygen formation. BRJ and betanin decreased the RNO absorbance at 440 nm by 12% and 9% after 45 min of irradiation, respectively. Furthermore, betanin interaction with Bcl-2 proteins was examined using binding free energy analysis and molecular dynamic simulation. The results revealed favorable interactions with ΔG values of −40.94 kcal/mol. Then, BRJ, betanin, Lip-BRJ, and Lip-Bet were tested as photosensitizers on normal (HEK 293) and human lung cancer (A549) cell lines. Irradiation significantly enhanced the cytotoxicity of Lip-Bet on HEK 293 cells (20% cell viability at 2000 µg/mL) and A549 cells (13% cell viability at 1000 µg/mL). For Lip-BRJ, irradiation significantly enhanced the cytotoxicity on HEK 293 cells at lower concentrations and on A549 cells at all tested concentrations. These results proved the positive effect of light and liposomal encapsulation on the anticancer activity of betanin and BRJ, suggesting the efficiency of liposomal beetroot pigments as green photosensitizers.